The effect of Genially Assisted PBL toward Internet accesbility on Elementary School Science HOTS Skills - Irdalisa Irdalisa; Rahmita; Budhi Akbar (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2026)
This research aimed to investigate the impact of the Genially-integrated Problem-Based Learning (PBL) model and levels of internet accessibility on the Higher-Order Thinking Skills (HOTS) of fourth-grade students, specifically regarding the topic of energy transformation. Utilizing a quasi-experimental method with a 2 x 2 factorial design, the study analyzed the interaction between the PBL model, students' internet access (categorized as high or low), and their cognitive outcomes. Data were collected via a 40-item multiple-choice HOTS test, which was validated using the Point Biserial Correlation formula. The hypothesis testing yielded an F-value of 4.76, surpassing the F-table threshold of 4.113; consequently, the null hypothesis was rejected in favor of the alternative, confirming that Genially-assisted PBL significantly influenced students' HOTS.  The second hypothesis test resulted in an F-value of 0.01, which is smaller than the F-table value of 4.113 (0.01 < 4.113). Thus, the null hypothesis (Ho) was accepted and the alternative hypothesis (H1) was rejected, meaning that students’ internet accessibility did not significantly affect their HOTS. The third hypothesis test yielded an F-value of 1.95, which is smaller than the F-table value of 4.113 (1.95 < 4.113). Therefore, the null hypothesis ($H_0$) was accepted, while the alternative hypothesis ($H_1$) was rejected, demonstrating that there was no significant interaction between the Genially-integrated Problem-Based Learning model and the students' Higher-Order Thinking Skills.